Breastfeeding and breast cancer risk: a case control study in Terengganu, Malaysia - Abd Alla Yousseff, Nivin Essameldin (2015)
Cancer breast is a growing problem in the community of Malaysia and all over the world. It is considered one of the fatal health problems. It is the most common cancer among female population in both developed and developing countries. (Globacon, IARC, 1008) Similarly, in Malaysia, it is the most common form of cancer affecting women, about 1 in 19 women are at risk of having cancer breast The Ministry of Health in Malaysia promotes breastfeeding as it is very beneficial to both the mother and the baby. It was found from many literatures done in other places over the world that breastfeeding will significantly decrease the risk of cancer breast for the mother and even the child,. It has been found that the relation is strongly affected by the duration of breastfeeding. So accordingly, it is important to do a study in Terengganu, as it was not done before, to find if the relation matches with the results in other countries. Hospital Sultanah Nur Zahirah (HSNZ) is chosen as it is the main referral hospital in Terengganu.